The Use Of Video Media In Improving Futsal Basic Techniques Skills Of Male Students Of Futsal Hobbyist - Adi Surya Hutomo; Agus Kristiyanto; Sapta Kunta Purnama (Kazimierz Wielki University, 2019)
This study aims to determine the improvement of basic futsal techniques skills through the use of video media for male students of futsal hobbyists. The selected sample is 15 players with random sampling technique. this research is using experimental method. Data collection is carried out by test and documentation techniques. Data analysis using t test. The results showed that the use of video media had a significant effect on futsal basic techniques skills (tcount = 5.887> ttable 5% = 2.145) with an increase of 38.30%. Based on the t test, it can be concluded that the use of video media can improve futsal basic techniques skills for male students of futsal hobbyists.